60 years of the Colworth Medal. (10th March 2023) - Ollett, Lucy
Abstract : The Colworth Medal is an esteemed annual award for outstanding research by a young biochemist of any nationality who has carried out the majority of their work in the UK or Republic of Ireland. Donated in 1963 by Unilever Research Colworth Laboratory, the award is made to an early-career scientist who is within 10 years of receiving their highest qualification. Interviews with past winners from 1963 to 2013 were previously published throughout 2013. To celebrate the 60th anniversary of the Colworth Medal, interviews with our latest winners will appear in The Biochemist throughout 2023. In this issue, we will hear from Dr M. Madan Babu (2014) and Professor Helen Walden (2015).